ضوابط تطبيقات بيع وسلف في خطاب الضمان المصرفي = Guidelines for the application of purchase (BayÑ)and loan (Salaf) in the Bank Letter of Guarantee - Abdullah, Mohd Muiz; Awang, Abdul Bari (2018)
Currently, rapid development in the Islamic financesector is aimed to fulfill people’sneeds. Because of that, Islamic banks needto produce new products and services with combined contracts which do not confine to a single contract. So, this research is made to identify the reasons of prohibition of the combination of purchase contract (bayÑ) and loan contract (salaf) mentioned in a ḥadtīh. One of these reasons isthe combination of two contracts in a single transaction that has been abundantly discussed by the scholarsin the past and present. A present example of the combined contracts produced by the newly created financial transactionsis “Letter of Guarantee,” where the researchers have found that this contract has been formed by combining twocontracts in a single transaction, i.e., bayÑand salaf. It is, therefore,necessary to understand the mentioned ḥadīth profoundly before its application in the Islamic banks so that it does not contradictthe holy SharīÑah. The researchers use the data collection method for collecting materials related to the subject of the study. They also use the analytical method to analyze the aḥādīthrelated to the topic,andthen investigatethe legitimacy of the applicationof bayÑand salaf in the “Letter of Guarantee,” and its juristicadaptation (takyīf fiqhī). An important finding of this research isthat the application of bayÑand salaf in the “Letter of Guarantee” is permitted, as long asthe higher objectives of SharīÑah are consideredin it, andthere isno involvement with the prohibited things